1991
DOI: 10.1002/jcp.1041470110
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of ATP‐induced hyperpolarization in renal epitheloid MDCK‐cells

Abstract: Previous studies have shown that ATP enhances intracellular calcium concentration and activates potassium channels in Madin Darby canine kidney (MDCK)-cells, thus leading to hyperpolarization of the cell membrane. The present study has been performed to elucidate the intracellular mechanisms involved. To this end, the effects of ATP on the potential difference across the cell membrane (PD), on formation of inositol phosphates, and on intracellular calcium concentration (Cai) have been analyzed in cells without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Transient elevation of [Ca 2ϩ ] i during 2-5 min of ATP addition has been documented in different subtypes of MDCK cells (20,34,35), including C11 cells (24). We observed that [Ca 2ϩ ] i response in C11 cells treated with ATP in medium A was slightly attenuated in the absence of extracellular Ca 2ϩ but was almost completely abolished in cells loaded with the intracellular Ca 2ϩ chelator BAPTA (Fig.…”
Section: Kinetics Of Nkcc Modulation By Extracellular Atp-treatment Wmentioning
confidence: 56%
“…Transient elevation of [Ca 2ϩ ] i during 2-5 min of ATP addition has been documented in different subtypes of MDCK cells (20,34,35), including C11 cells (24). We observed that [Ca 2ϩ ] i response in C11 cells treated with ATP in medium A was slightly attenuated in the absence of extracellular Ca 2ϩ but was almost completely abolished in cells loaded with the intracellular Ca 2ϩ chelator BAPTA (Fig.…”
Section: Kinetics Of Nkcc Modulation By Extracellular Atp-treatment Wmentioning
confidence: 56%
“…Two additional lines of evidence indicate that store-operated channels make, at most, a minor contribution to the RGD-induced influx. First, we found that the magnitude of [Ca21]i transients resulting from ATP stimulation is similar in the presence or absence of external calcium, suggesting that, although it is substantial in other clones (Paulmichl et al, 1990), stimulation of store release does not trigger a large store-operated influx component in the clone of cells we have used. Second, we can rule out the possibility that RGD beads induce a rapidly inactivating storeoperated Ca21 influx mechanism like that triggered by TG, because that influx was Ni2+-insensitive, unlike the RGD bead response, which is Ni2+-sensitive (Figure 8b).…”
Section: Inhibition Of Rgd-induced Signaling and Cell Adhesion With Caimentioning
confidence: 83%
“…Thus, in the present study we focused on mechanisms that elicit the initial sharp increase in [Ca2+]i (the RGDinduced [Ca2+]i "transient"). Both bead adhesion and calcium signaling are specific to RGD and are decreased by antibodies that inhibit the function of av133 and avP35 integrins (Sjaastad et al, 1994 We examined the dependence of (Paulmichl et al, 1990). Ca2+ release occurs because of activation of phospholipase C and generation of IP3 via a phorbol ester and pertussis toxin-sensitive mechanism (Paulmichl et al, 1990 , 1993), tyrosine phosphorylation-dependent activation of phospholipase C (Kanner et al, 1993;Blake et al, 1994;Somogyi et al, 1994), and production of IP3 (Sultan et al, 1991;Somogyi et al, 1994 (Hill et al, 1987;Ghosh et al, 1988;Harootunian et al, 1991).…”
Section: Adhesion Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies showed that ATP and UTP hyperpolarise MDCK cells by increasing the K + conductance [95,206]. A later paper from this group showed that ATP increased [Ca 2+ ] i ; calcium then activates K + channels and thus leads to hyperpolarisation of the cell membrane [281]. Regulation of transepithelial ion transport by two different receptors on the apical membrane of MDCK cells was claimed [430], the data implicating P2Y 1 and P2Y 2 (or P2Y 4 ) receptors.…”
Section: Distal Tubulesmentioning
confidence: 99%